Pengaruh Employee Engagement, Pelatihan Digital dan Sistem Reward terhadap Produktivitas Pegawai Badan Pusat Statistik Kabupaten Kediri - Ismi Rojayanti; Erwin Syahputra; Heru Sutapa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the influence of employee engagement, digital training, and reward systems on employee productivity at the Central Statistics Agency of Kediri Regency. The research adopts a quantitative approach with a questionnaire as the primary data collection tool. A total of 33 employees participated as respondents, determined using a saturated sampling technique, which ensures that all members of the population were included. The instrument utilized was a Likert-scale questionnaire, designed to capture perceptions and experiences related to engagement, training, and rewards. The data were analyzed using multiple linear regression to measure both the partial and simultaneous effects of the independent variables on productivity. The results reveal that employee engagement plays a significant role in enhancing productivity, with a significance value of 0.003. Similarly, digital training and reward systems also exert a positive and significant influence, with significance values of 0.037 and 0.0002, respectively. When tested simultaneously, the three independent variables collectively demonstrate a substantial impact on employee productivity, as evidenced by an F-value of 76.069. Furthermore, the Adjusted R Square value of 87.6% indicates that the research model possesses strong explanatory power, meaning that most variations in productivity can be explained by employee engagement, digital training, and reward systems. These findings highlight the strategic importance of integrating engagement initiatives, continuous digital skill development, and fair reward mechanisms to foster higher levels of productivity. For organizations, particularly government institutions, the study underscores the necessity of adopting a holistic human resource development framework that addresses both intrinsic and extrinsic motivational factors to maximize employee performance.